Inhibitory Effect of Lactobacillus delbrueckii subsp. bulgaricus KSFY07 on Kappa-Carrageenan-Induced Thrombosis in Mice and the Regulation of Oxidative Damage - Pan Wang; Fang Tan; Jianfei Mu; Hongjiang Chen; Xin Zhao; Yanan Xu (Cardiovascular Therapeutics)
A mouse thrombosis model was established by kappa-carrageenan to observe the inhibitory effect of Lactobacillus delbrueckii subsp. bulgaricus KSFY07 (LDSB-KSFY07) on thrombosis and the oxidative stress response. Mouse serum, liver tissue-related indicators, and intestinal microbial composition were measured by examining the expression of microbes in mouse faeces using a biochemical kit, slice observations, and quantitative polymerase chain reaction (qPCR) experiments. The results showed that LDSB-KSFY07 effectively reduced the degree of black tail in thrombotic mice, increased activated partial thromboplastin time (APTT), and decreased thrombin time (TT), fibrinogen (FIB), and prothrombin time (PT) in thrombotic mice. LDSB-KSFY07 was also able to reduce malondialdehyde (MDA) levels and increase superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) levels in the serum and liver tissues of thrombotic mice. Pathological observations showed that LDSB-KSFY07 reduced liver tissue lesions and tail vein thrombosis. Further, experimental results showed that LDSB-KSFY07 was able to upregulate the mRNA expression of copper/zinc-SOD (Cu/Zn-SOD), manganese-SOD, and GSH-Px in the liver tissue of thrombotic mice. Moreover, LDSB-KSFY07 was also able to downregulate the mRNA expression of NF-κB p65, intercellular cell adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and E-selectin in tail vein vascular tissue. Meanwhile, LDSB-KSFY07 could raise plasminogen activator inhibitor-1 (PAI-1) mRNA expression and reduce tissue plasminogen activator (t-PA) expression in heart and tail vein vascular tissues of thrombotic mice. A mouse faeces examination revealed that LDSB-KSFY07 could also upregulate Bacteroides, Lactobacterium, and Bifidobacterium microbial expression and downregulate Firmicutes expression in the gut. These results indicate that LDSB-KSFY07 was able to inhibit mouse thrombosis and reduce liver oxidative stress damage in thrombus mice and show that high concentrations of LDSB-KSFY07 provided a better response similar to that of the drug heparin.